Metabolomics profiling and antioxidant analysis of enzymatically treated Okara fermented by Lactobacillus plantarum SY11 - Lim, Siew Khim; Rosma Ahmad; Pongsathon Phapugrangkul; Siti Nur Hazwani Oslan; Lau, Nyok-Sean; Sixu-Gong; Tan, Joo Shun (Elsevier Ltd., 2025)
Okara, a major industrial by-product of soymilk production, can be sustainably repurposed as a cost-effective and environmentally friendly fermentation substrate. Lactic acid bacteria (LAB) fermentation is being used to enhance nutritional profile in fermented food. In this study, three LAB starters, namely Lactobacillus acidophilus TP7, L. casei ATCC 393, and L. plantarum SY11 were screened based on viable cell count and total protein content after 48 h fermentation on enzymatic treated okara (ETO). Among the three strains, L. plantarum SY11 had the highest viable cell count (16.40 ± 0.06 log CFU/mL) and protein content (14.76 ± 0.24 %), with protein content significantly higher (p < 0.05) than L. acidophilus TP7 (13.59 ± 0.16 %). L. casei ATCC 393 had the lowest viable cell count (13.27 ± 0.06 log CFU/mL), significantly lower (p < 0.05) than the other two strains. In total, 55 metabolites were detected and classified mainly into organic acids, fatty acids, amino acids, carbohydrates, alcohols, aldehyde, phytosterol, and miscellaneous groups. Fermented okara (FO) exhibited a 2.54-fold increase in DPPH, a 2.31-fold increase in ABTS, and a 2.84-fold increase in FRAP antioxidant activity compared to raw okara (RO), indicating a significant enhancement in its antioxidant properties after fermentation. These findings suggest that FO could serve as a functional food, providing a symbiotic ingredient with promising food and feed applications.